Epidemiology of occupational and environmental risk factors related to ovarian cancer - Shen, N.; Weiderpass, Elisabete; Anttila, Ahti; Goldberg, M. S.; Vasama-Neuvonen, K. M.; Boffetta, Paolo; Vainio, H. U.; Partanen, T. J. (Scandinavian Journal of Work, Environment & Health, 1998)
This paper reviews articles published during 1970-1997 from 48 epidemiologic studies on occupational and environmental risk factors of ovarian cancer. Current evidence is characterized by poorly focused data for occupational and environmental agents, vulnerability to biases, and an almost complete lack of quantitative exposure-response data. The moderate amount of data on nurses, teachers, professionals, dry cleaning employees, women in agriculture, pharmaceutical industry, pharmacists, waitresses, and cooks show very little, if any, evidence of excess risk. Hairdressers, beauticians, and women employed in the printing industry may be at increased risk, but the data are insufficient for strong conclusions. Some case-referent studies suggest a modest-to-moderate excess in association with genital talc application. Few high-quality studies have been carried out, and no chemical agents have been studied extensively, with the exception of exposure to talc. Ovarian cancer may have occupational and environmental etiologies intertwined with cultural, behavioral, and life-style factors and genetic susceptibility, but current knowledge is insufficient to quantify occupational and environmental etiologies reliably. Well-designed analytic epidemiologic studies with sufficient power are needed.
Keywords: etiology; exposure; occupation; ovarian neoplasms; review